2017
DOI: 10.1186/s12961-017-0181-0
|View full text |Cite
|
Sign up to set email alerts
|

International consultation on long-term global health research priorities, research capacity and research uptake in developing countries

Abstract: BackgroundIn recognition of the need for long-term planning for global health research, and to inform future global health research priorities, the United Kingdom Department for International Development (DfID) carried out a public consultation between May and June 2015. The consultation aimed to elicit views on the (1) the long-term future global health research priorities; (2) areas likely to be less important over time; (3) how to improve research uptake in low-income countries; and (4) how to build researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Research not always used to inform policy and practice decisions [48][49][50][51][52][53][54][55][56] Examples of LMIC researchers successfully getting evidence used [43,48,49] Factors influencing KT Researchers' reputation/credibility/contextual understanding [32,49,50,[57][58][59][60][61][62][63][64][65][66][67][68]127] Relevance and credibility of research evidence [32, 49, 50, 53, 54, 58, 60, 62-67, 70-72, 127] Contrasting views, demands and incentives among researchers and policy-makers in relation to research, its use, policy actor roles and policy-making [32, 49, 50, 57, 59-61, 67, 70, 73-78] Nature of policy issues (technical versus contested versus interest of policy-maker) [49, 58-62, 67, 70, 76, 79] Political context [32, 48-51, 53, 58, 59, 62, 64, 67, 80, 81, 127] Decision-makers' research background [51,55,57,65,77] Donor influence [51, 54, 55, 57-60, 70, 71, 127] International influence, e.g. WHO [54,58,59,65,67,…”
Section: Research Usementioning
confidence: 99%
See 2 more Smart Citations
“…Research not always used to inform policy and practice decisions [48][49][50][51][52][53][54][55][56] Examples of LMIC researchers successfully getting evidence used [43,48,49] Factors influencing KT Researchers' reputation/credibility/contextual understanding [32,49,50,[57][58][59][60][61][62][63][64][65][66][67][68]127] Relevance and credibility of research evidence [32, 49, 50, 53, 54, 58, 60, 62-67, 70-72, 127] Contrasting views, demands and incentives among researchers and policy-makers in relation to research, its use, policy actor roles and policy-making [32, 49, 50, 57, 59-61, 67, 70, 73-78] Nature of policy issues (technical versus contested versus interest of policy-maker) [49, 58-62, 67, 70, 76, 79] Political context [32, 48-51, 53, 58, 59, 62, 64, 67, 80, 81, 127] Decision-makers' research background [51,55,57,65,77] Donor influence [51, 54, 55, 57-60, 70, 71, 127] International influence, e.g. WHO [54,58,59,65,67,…”
Section: Research Usementioning
confidence: 99%
“…KT knowledge and skills of target audiences Sensitise and train target audiences on the value of research use in decision-making and research methods [31,50,51,56,57,62,64,67,70,74,75,78,84,85] Research availability, accessibility and relevance Rapid response service, strategic consultancy and research commissions for policy institutions and donors/funders [49,53,57,59,61,64,67,77,87,127] Produce a mix of research evidence, including operations research, systematic reviews, effectiveness and cost-effectiveness research, develop low cost innovations to improve practice, etc.…”
Section: Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of knowledge and skills have been identified as primary barriers to the use of ICT tools among health researchers in resource-limited settings [10][11][12], and there is an increasingly recognized need for improved access to ICT training opportunities for health researchers worldwide. It is clear that international collaboration is vitally important for building research capacity in resource limited academic centers [13], and also clear that ICT tools can improve the efficiency of multinational research projects that span cultures, languages and time zones [14,15]. As such, international collaborations may both facilitate training surrounding the use and integration of ICT tools and also support the research resulting from increased utilization of the tools [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…ICT is gradually becoming an integral part of the learning and teaching environment in most medical schools, and has translated some important theories on student learning into reality in professional settings [5]. Additionally, for the faculty members involved in education and research, grasping ICT skills has been identified as a key and challenging step in long-term global health research [13,14], and they are often required to change the technologies in the teaching process. Moreover, the promotion of ICT can help faculty members to better accept the changes and needs brought by new technologies.…”
mentioning
confidence: 99%